'Non-criteria antiphospholipid antibodies': bridging the gap between seropositive and seronegative antiphospholipid syndrome. (10th May 2021) - Truglia, Simona; Mancuso, Silvia; Capozzi, Antonella; Recalchi, Serena; Riitano, Gloria; Longo, Agostina; De Carolis, Sara; Spinelli, Francesca Romana; Alessandri, Cristiano; Ceccarelli, Fulvia; De Carolis, Caterina; Misasi, Roberta; et al.
Abstract: Objective: We aimed to analyse the prevalence of non-criteria anti-phospholipid (aPL) antibodies and their role in the diagnosis, treatment and prognosis in a cohort of patients with clinical features consistent with a diagnosis of antiphospholipid syndrome (APS), but persistently negative for criteria aPL – anti-cardiolipin antibodies (aCL), anti-β2-glycoprotein I antibodies (aβ2-GPI) and lupus anticoagulant (LA) – named seronegative APS (SN-APS). Methods: Sera from SN-APS patients were tested for aCL by TLC-immunostaining, anti-vimentin/cardiolipin (aVim/CL) and anti-phosphatidylserine/prothrombin (anti-PS/PT) by ELISA. Control groups of our study were APS patients and healthy controls. Results: We enrolled 114 consecutive SN-APS patients, 69 (60.5%) resulted positive for at least one non-criteria test in two occasions 12 weeks apart. Among the persistently positive patients to these tests, 97% resulted positive for aCL by TLC-immunostaining, 52.3% for aVim/CL and 17.4% for aPS/PT. SN-APS patients with double positivity (aCL by TLC-immunostaining and aVim/CL) showed a likelihood positive ratio of 8 to present mixed thrombotic and obstetrical features. Among SN-APS patients tested positive, after the therapeutic changes, three cases of recurrent thrombosis were observed [median follow-up 41 months (IQR 39.5)]. Twenty pregnancies were recorded in 17 SN-APS patients after the detection of unconventional aPL and 12 of them (60%) experienced a good outcome under conventional treatment for APS. Conclusions: This is the largest monocentric study demonstrating that aCL tested by TLC-immunostaining and aVim/CL can detect aPL positivity in SN-APS. It may encourage clinicians to monitor and provide adequate targeted therapy, which improve SN-APS prognosis.